Impact of micronutrients on upland rice yield, Nicaragua - Siles, Pablo; Tellez, Orlando; Peng, Yuan-Ching; Zeledón, Yasser (International Center for Tropical Agriculture, 2020)
This dataset contains information of experiments carried out upland rice in two regions of Nicaragua (Caribbean and Pacific Region), as well as a compilation of soils data from different regions in Nicaragua collected from 2015 to 2019. The experiments were designed to explore the effects of micronutrients in the yield of upland rice. The experiments were carried out on farmer’s field during the 2018 production cycle, the dataset contains yield and aerial biomass of the experiments.